Intermarriage from Central Europe to Central Asia : mixed families in the age of extremes - Edgar, Adrienne Lynn, 1960- (Borderlands and transcultural studies., 2020)
"Edgar and Frommer bring together international and interdisciplinary scholarship to analyze interethnic and interracial marriage in Eastern Europe, the former Soviet Union, and Central Asia"--